Intrauterine death: an approach to the analysis of genetic heterogeneity. Issue 3 (June 1983) - Bottini, E; Coromaldi, L; Carapella, E; Pascone, R; Nicotra, M; Coghi, I; Lucarini, N; Gloria-Bottini, F
Abstract : A study of survival time of zygotes in utero and the relationship with parental phenotype of a series of genetic polymorphisms was carried out in 41 couples with habitual abortion. Variability of intrauterine survival time was found to be much higher between families than within families suggesting that several genetic entities contribute to the condition clinically defined as habitual abortion. Significant differences of survival time were found in relation to the length of the paternal Y chromosome and to the maternal phenotypes of PGM1 and Ss. These observations are in line with previous data suggesting intrauterine selection in these polymorphisms. Further studies of the timing of intrauterine death in relation to 'normal' genetic polymorphisms may help to clarify the aetiology of spontaneous fetal loss.